2019
DOI: 10.3390/dj7010014
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Different Dentifrice Compositions for Increasing the Hardness of Demineralized Enamel: An in Vitro Study

Abstract: This study aimed to evaluate microhardness of a dentifrice containing fluoride and arginine compared to a positive control (fluoride only) and a negative control (no fluoride) on sound and demineralized bovine enamel surfaces. Specimens were randomly assigned to different treatments that included daily pH cycling and brushing three times a day with one of the following dentifrices (n = 8): Neutraçucar (arginine and fluoride), Colgate Total 12 (fluoride) and My First Colgate (no fluoride). Enamel carious lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Besides that, the fluoride present in this dentifrice promoted the formation of calcium fluoride deposits on the enamel surface (Crastechini et al, 2019;Featherstone et al, 1982). Oliveira et al (2019) study showed that arginine-based dentifrices increase the microhardness of sound and demineralized bovine enamel surfaces and reported that the mechanism involved was the presence of free calcium ions in the oral environment make the saliva super-saturated and favor remineralization, despite the negative charge in demineralized hydroxyapatite crystals.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Besides that, the fluoride present in this dentifrice promoted the formation of calcium fluoride deposits on the enamel surface (Crastechini et al, 2019;Featherstone et al, 1982). Oliveira et al (2019) study showed that arginine-based dentifrices increase the microhardness of sound and demineralized bovine enamel surfaces and reported that the mechanism involved was the presence of free calcium ions in the oral environment make the saliva super-saturated and favor remineralization, despite the negative charge in demineralized hydroxyapatite crystals.…”
Section: Discussionmentioning
confidence: 96%
“…However, caution has to be taken when extrapolating these results to clinical conditions. Arginine based dentifrices were also introduced as a possibility to protect teeth against erosion and caries (Aguiar et al, 2017;Oliveira et al, 2019;West et al, 2017). Despite the positive results obtained with arginine addition, stannous fluoride (SnF2) based dentifrices showed superiority for protecting human teeth against the initiation and progression of dental erosion (West et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…et al, (30) and Oliveira. et al, (36) in which results showed that fluoride and arginine could increase the microhardness of sound and demineralized bovine enamel surfaces. It is possible that arginine-fluoride complexes could have been stored within enamel, 205…”
Section: Groupsmentioning
confidence: 97%